Anterior cruciate ligament injuries in female athletes: Why are women more susceptible? - Moeller, J. L.; Lamb, M. M. (The Physician and Sportsmedicine, 1997)
Anterior cruciate ligament (ACL) injuries occur most frequently in planting and cutting sports such as basketball, soccer, and volleyball. National Collegiate Athletic Association injury data show that female athletes injure the ACL more frequently than their male counterparts do. The greater incidence of ACL injuries in women probably stems from complex, interrelated factors, possibly including hamstring-quadriceps strength imbalances, joint laxity, and the use of ankle braces. Successful treatment often includes surgery.